Hubungan Antara Persepsi Terhadap Penempatan Kerja Dengan Prestasi Kerja Karyawan Pada PT.Tugu Beton Semesta Abadi Semarang - Nurwahyuni, Annisa; , Drs. Mohammad Amir, M.Si (2017)
The development of the company or industry relies on human resources (HR). Employees have a very large function within the company where the planning, execution, and control iscarried out by employees. Under these conditions, the success and progress of an industry heavily influenced by the work performance of employees.The purpose of this study to determine the relationship between perceptions of employment with employee performance.The sample in this study were employees of PT.Tugu Beton Semesta Abadi who worked on the staff that consist of 120 people and selected by purposive sampling technique.The method used in this research is quantitative method,Methods of data collection using the documentation of work performance and job placement perception scale.Data analysis techniques using Pearson product Moment Correlation.The results show that (1) There is a significant positive relationship between perceptions of employment with employee performance, (2) The research subjects have perceptions of employment that was classified in high category, (3) The research subjects have work performance that was classified in high category, and (4) Effective contribution to the perception of employment with employees performance of 5.15%.